2023
DOI: 10.1002/aenm.202203756
|View full text |Cite
|
Sign up to set email alerts
|

Dopant‐Free Two‐Dimensional Hole Transport Small Molecules Enable Efficient Perovskite Solar Cells

Abstract: due to their advantages of high performance, low cost, and easy fabrication of large-scale flexible devices. [5][6][7][8] The primary obstacle hindering their commercial applications is the stability issue. [9,10] So far, the 2,2″,7,7″-tetrakis-(N,N-dip-methoxyphenylamine)-9,9′-spirobifluorene (Spiro-OMeTAD) has become the dominated hole transport material (HTM) in n-i-p PSCs. The deliquescent dopants, such as 4-tertbutylpyridine (TBP) and lithium bis(trifluoromethyl sulfonyl) imide (LiTFSI), are required to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…These features indicate a strong interaction between perovskite and FOA due to the chemical reaction between Pb 2+ and oxalate (Figure S16, Supporting Information). [32,49] The electron-only devices with the structure of ITO/SnO 2 /perovskite/PC 61 BM/Ag were fabricated to evaluate the trap density of perovskite deposited on different substrates. The current-voltage curves of electron-only devices in dark revealed that the corresponding N t s were determined to be 1.89 × 10 15 and 4.02 × 10 14 cm −3 for the SnO 2 and SnO 2 -FOAbased devices, respectively (Figure 4g).…”
Section: Resultsmentioning
confidence: 99%
“…These features indicate a strong interaction between perovskite and FOA due to the chemical reaction between Pb 2+ and oxalate (Figure S16, Supporting Information). [32,49] The electron-only devices with the structure of ITO/SnO 2 /perovskite/PC 61 BM/Ag were fabricated to evaluate the trap density of perovskite deposited on different substrates. The current-voltage curves of electron-only devices in dark revealed that the corresponding N t s were determined to be 1.89 × 10 15 and 4.02 × 10 14 cm −3 for the SnO 2 and SnO 2 -FOAbased devices, respectively (Figure 4g).…”
Section: Resultsmentioning
confidence: 99%
“…47,48 Interface passivation is a simple and effective method for improved charge carrier transport, reduced nonradiative recombination, and enhanced PCE. 49,50 To achieve more efficient and stable 2D RP PSCs, we propose a predeposition transport layer (PDTL) strategy aimed at passivating the surface defects and enhancing the ETL properties through the establishment of a reinforced PCBM coverage over the perovskite layer. The flowchart outlining the PDTL processing is shown in Figure 2a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…6 Compared to r-PSCs, the i-PSCs possess advantages of negligible photocurrent hysteresis, low-temperature preparation technology, and splendid compatibility in fabricating flexible and tandem cells. 7 Both r-PSCs and i-PSCs are fabricated as a sandwiched combination of electron transport materials, perovskite absorber, hole transport materials (HTMs), and electrodes, in which the HTM layers are indispensable in facilitating hole extraction/transport and restraining charge recombination occurring at the perovskite/charge transport interfaces. 8−10 Thus, a successful hole transport material should have the characteristics of high mobility, good film-forming property, energy level matching, high stability, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The film morphology of HTMs plays a vital role in device efficiency and stability as it significantly affects the perovskite crystallization because the perovskite absorber is coated on the surface of the HTM layer. 7,9,11,13 A host of reported HTMs are applicable only for either r-PSCs or i-PSCs (e.g., spiro-OMeTAD is superior in r-PSCs, while performs poorly in the i-PSCs), which quite increases the research cost of devices and is not conducive to mass production. Therefore, seeking efficient HTMs performing well in both r-PSCs and i-PSCs is urgently needed, and the key for achieving this goal is in well modulating the two key elements (i.e., film morphology and hole mobility).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation